ENHANCING THE PRODUCTIVITY OF SMALL FARMERS IN CROATIA THROUGH THE AGRICULTURAL FUND FOR RURAL DEVELOPMENT - Hadelan, Lari; Zrilić, Marija; Jež Rogelj, Mateja; Zrakić Sušac, Magdalena (Economics of Agriculture, 2022)
Since 2015, investment subsidies from the EAFRD through the Rural Development Program have been available to farmers in Croatia. The most numerous holdings in Croatia are those with an economic size of up to 8,000 euros, characterized by a low level of productivity due to insufficient production capacity and inadequate machinery They are the intended aid recipients in the sub-measure 6.3. In the three tenders held so far, this sub-measure has been mostly used for the purchase of machinery (62% of all users), which most often includes old tractors inadequate for modern agricultural production. The increase in production capacity with the growth of the Standard Output was used by only 38% of sub-measure users , with a slightly higher share of young farmers and those working in ﬂower production. The conclusion of the paper is that in order to increase the productivity of small farmers, it is necessary to redefine the criteria for approving applications in sub-measure 6.3 in a way that preference is given to farmers committing to activities that will increase their production capacity and Standard Output.